The Affect Of Clean And Healthy Living Behavior (PHBS), Economic Level And Parenting Patterns On The Risk Of Stunting Incidence In The Working Area Of UPT Puskesmas Bereng - Adhi Wijaya Siswanto; Abdullah Syafei (Jurnal EduHealth, 2024)
Stunting is a condition of growth failure in children under five due to chronic malnutrition so that children become too short for their age. The short-term impact of stunting is susceptibility to infectious diseases while the long-term impact is the inhibition of physical and cognitive development. This study aims to determine the effect of Clean and Healthy Living Behavior (PHBS), economic level and parenting patterns on the risk of stunting in the work area of UPT Puskesmas Bereng. This is an observational study, quantitative design with a cross sectional approach. The study population was all 216 toddlers aged 6-23 months. Sampling was done by cluster random sampling with a total of 140 toddlers 6-23 months. Univariate analysis was conducted to describe each variable studied. The chi-square test was used for bivariate analysis and multivariate analysis was performed by binomial logistic regression model test. The results showed that clean water sources (p = 0.001 OR 7.812), exclusive breastfeeding (p = 0.006 OR 5.898), healthy latrines (p = 0.016 OR 4.991), family economic level (p = 0.029 OR 0.224) and parenting (p = 0.001 OR 3.518) significantly influenced the risk of stunting in toddlers 6-23 months. Whereas delivery in health facilities (p = 0.285 OR 0.463), weighing infants and toddlers regularly (p = 0.053 OR 5.131), washing hands with soap and clean water (p = 0.992 OR 1.014), consumption of nutritious healthy food (p = 0.230 OR 2, 139), regular physical activity (p = 0.892 OR 0.894), family members who smoke (p = 0.552 OR 0.690) and eradicate mosquito nests (p = 0.264 OR 1.955) do not significantly affect the risk of stunting in toddlers under 6-23 months. In the interpretation of the odds ratio, clean water sources (OR 7.812) have a greater effect than other variables on the risk of stunting in toddlers under 6-23 months.